2015
DOI: 10.1118/1.4907963
|View full text |Cite
|
Sign up to set email alerts
|

Image quality dependency on system configuration and tube voltage in chest tomosynthesis—A visual grading study using an anthropomorphic chest phantom

Abstract: At the standard dose level of the VolumeRAD system, the potential benefits from increasing the dose per projection do not fully compensate for the negative effects resulting from a reduction in the number of projection images. Consequently, the default configuration consisting of 60 projection images acquired over 30° is a good alternative. The tube voltage used in tomosynthesis does not have a large impact on the image quality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 63 publications
1
12
0
Order By: Relevance
“…Table 4 shows that all protocols with a swing angle ,20°resulted in a significantly lower rating than the reference protocol (swing angle 27°) for this class of criteria and that the smaller the swing angle, the lower the AUC VGC . This result agrees well with Söderman et al 33 who reported that for a criterion related to the possibility to follow vessels through the volume all protocols with a swing angle ,20°r esulted in a lower image quality than their reference (swing angle 30°). For the demarcation class of criteria, on the other hand, no strong dependency on the swing angle was seen in the present study.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Table 4 shows that all protocols with a swing angle ,20°resulted in a significantly lower rating than the reference protocol (swing angle 27°) for this class of criteria and that the smaller the swing angle, the lower the AUC VGC . This result agrees well with Söderman et al 33 who reported that for a criterion related to the possibility to follow vessels through the volume all protocols with a swing angle ,20°r esulted in a lower image quality than their reference (swing angle 30°). For the demarcation class of criteria, on the other hand, no strong dependency on the swing angle was seen in the present study.…”
Section: Discussionsupporting
confidence: 82%
“…In chest DTS, a projection image density of two (images per degree) has been recommended, as the ribs (being significant high-contrast structures) may be at a considerable distance from certain reconstructed planes, 4 especially for larger patients. Söderman et al 33 who performed a study similar to the present study (an evaluation of image quality based on the reproduction of an anthropomorphic chest phantom at different acquisition protocols) on the GE chest DTS system reported an increase in image artefacts with decreasing projection image density. This was especially evident for projection image densities ,1 (projection image densities down to 0.5 were investigated).…”
Section: Discussionmentioning
confidence: 74%
“…The tube voltage was 120 kV. These acquisition parameters have been found optimal for chest tomosynthesis ( 24 ) .…”
Section: Methodsmentioning
confidence: 99%
“…Sixty projection radiographs were acquired within an angular range of §158 relative to the standard posteroanterior projection at a tube voltage of 120 kVp. These are the default settings for a chest tomosynthesis examination with this system and previous studies have shown that these settings result in adequate image quality (25,26). The scan time for the acquisition of the 60 projection images is 10 seconds.…”
Section: Image Collectionmentioning
confidence: 99%